Twenty Years Later: A Comprehensive Review of the X Chromosome Use in Forensic Genetics - Gomes, Iva; Pinto, Nádia; Antão-Sousa, Sofia; Gomes, Verónica; Gusmão, Leonor; Amorim, António (Frontiers in Genetics, 2020)
The unique structure of the X chromosome shaped by evolution has led into the present gender-specific genetic differences, which are not shared by its counterpart, the Y chromosome, and neither by the autosomes. In males, recombination between the X and Y chromosomes is limited to the pseudoautosomal regions, PAR1 and PAR2; therefore, in males, the X chromosome is (almost) entirely transmitted to female offspring. On the other hand, the X chromosome is present in females with two copies that recombine along the whole chromosome during female meiosis and that is transmitted to both female and male descendants. These transmission characteristics, besides the obvious clinical impact (sex chromosome aneuploidies are extremely frequent), make the X chromosome an irreplaceable genetic tool for population genetic based studies as well as for kinship and forensic investigations. In the early 2000s, the number of publications using X-chromosomal polymorphisms in forensic and population genetic applications increased steadily. However, nearly 20 years later, we observe a conspicuous decrease in the rate of these publications. In light of this observation, the main aim of this article is to provide a comprehensive review of the advances and applications of X-chromosomal markers in population and forensic genetics over the last two decades. The foremost relevant topics are addressed as: i) developments concerning the number and types of markers available, with special emphasis on short tandem repeat polymorphisms (STR nomenclatures and practical concerns); ii) overview of worldwide population (frequency) data; iii) the use of X-chromosomal markers in (complex) kinship testing and the forensic statistical evaluation of evidence; iv) segregation and mutation studies and; v) current weaknesses and future prospects.